Respuesta :

Answer:

Mistake -2(x+5)=-2x+10, -2(x+5)=-2x-10

Step-by-step explanation:

7(x-10)-2(x+5)=4x-7+6x-3

7x-70-2x-10=10x-10

5x-80=10x-10

-80+10=10x-5x

-70=5x

-70/5=x

-14=x

Answer:

• On the second step, while using the distributive property.

[tex]7x - 70 - 2x \: { \red{ + }} \: 10 = 10x - 10[/tex]

» the red plus is the mistake, it had to be -10 not positive 10

correction:

[tex]7x - 70 - 2x \: { \green{ - }} \: 10= 10x - 10[/tex]

further more:

[tex] - 5x = 50 \\ x = - 10[/tex]